The association of social and behavioral factors with dietary risks in adults: Evidence from the Kardiovize Brno 2030 study - Maugeri, A; Barchitta, M; Kunzova, S; Bauerova, H; Agodi, A; Vinciguerra, M (Nutrition, metabolism, and cardiovascular diseases, 2020)
BACKGROUND AND AIMS: Uncovering the main determinants of diet quality is one of the greatest challenges for Public Health, since it could guide future strategies and interventions against cardiovascular diseases (CVDs). The present cross-sectional analysis of the Kardiovize cohort evaluates the prevalence of dietary risk factors for CVDs and their association with social and behavioural characteristics in a random sample of 1536 adults (aged 25-64 years) from Brno, Czech Republic. METHODS AND RESULTS: A face-to-face health interview guided by structured questionnaires was carried out on socio-demographic characteristics (age, sex, educational level, employment, marital status, income, and household size) and behaviours (smoking status, physical activity, and sleep habits). Twelve dietary risk factors covered by the Global Burden of Diseases comparative risk assessment framework were assessed using a Food Frequency Questionnaire. In general, we observed that the consumption of nearly all healthy foods and nutrients was suboptimal, and that it was also aggravated by high intake of foods and nutrients that constituted dietary risk factors. Moreover, we found several associations of social and behavioural characteristics with specific dietary risk factors. Particularly, being male (β = 0.466; SE = 0.079; p < 0.001), increasing household size (β = 0.130; SE = 0.047; p = 0.006), low income (β = 0.192; SE = 0.091; p = 0.035), and decreasing physical activity level (β = 0.172; SE = 0.054; p = 0.002) were associated with increasing number of dietary risk factors. CONCLUSION: Thus, our study raises an urgent need for Public Health strategies promoting healthy eating in adulthood, which should be based on traditional and novel determinants of dietary risk.
Keywords: Sedentary Behavior; Cross-Sectional Studies; Sociodemographic factors; stravovací zvyklosti; Health Behavior; hodnocení rizik; Male; Risk Assessment; Risk Factors; sexuální faktory; Česká republika; zdravé chování; Behaviours; Adult; Age Factors; Feeding Behavior; Prospective Studies; dospělí; Public health; mužské pohlaví; sociální determinanty zdraví; Marital Status; Epidemiology; Employment; Exercise; Income; stupeň vzdělání; Smoking; dieta; Czech Republic; Nutritive Value; Sleep; nutriční hodnota; kardiovaskulární nemoci; lidé; sedavý životní styl; ženské pohlaví; zvyky; příjem; Educational Status; Humans; Sex Factors; spánek; rizikové faktory; průřezové studie; věkové faktory; Diet; Social Determinants of Health; zaměstnanost; Cardiovascular risk; manželský stav; Cardiovascular Diseases; Female; cvičení; Habits; lidé středního věku; kouření; Middle Aged; prospektivní studie